The Konitsa, Epirus-NW Greece, July 26 (Ms=5.4) and August 5, 1996, (Ms=5.7) earthquakes sequence - PAPANASTASSIOU, D. (Bulletin of the Geological Society of Greece, 2001)
On August 5, 1996, at 22:46 GMT (August 6, 01:46 local time), a strong shallow earthquake of Ms=5.7 occurred at the area of Konitsa, Epirus-northwestern Greece. The earthquake caused significant damage in the city of Konitsa as well as the neighbouring villages. In the same area on July 26, at 18:55 GMT (21:55 local time), another strong earthquake of Ms=5.4 had occurred, mainly causing damage at the lower part of Konitsa. In this study, data from seismological stations located in the broader area of NE Greece and neighbouring countries were used in order to study the spatial and temporal characteristics of this earthquake sequence. Focal mechanisms of the stronger shocks were also plotted. All the observations are combined, in order to obtain a better understanding of the regional tectonics and its seismic activity.